Implementasi Manajemen Mutu Terpadu dalam Pendidikan Islam: Sebuah Systematic Literatur Review tentang Resiliensi Lembaga dan Kepuasan Stakeholder - Yusnida Abila; Maftuhatul Afrah; Moch. Wildani Dwi Sulaiman; Mu’allimin Mu’allimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Improving the quality of education has become a crucial issue in the era of globalization, marked by increasing competition between institutions and public expectations for superior educational services. Integrated Quality Management (TQM) emerges as a strategic approach to improve the effectiveness, efficiency, and satisfaction of various educational stakeholders. This study aims to review the development of studies related to TQM implementation in education through a qualitative literature review. Data were collected from scientific articles published between 2020 and 2025 using Google Scholar and Publish or Perish with the keywords "TQM implementation in education." From the initial 30 articles, five of the most relevant main articles were selected. The analysis revealed three main themes: (a) the application of TQM to strengthen institutional resilience, (b) the integration of Islamic values ​​in quality management, and (c) the challenges and opportunities of TQM in vocational education. This study concluded that the stakeholder satisfaction dimension remains underexplored and requires further empirical research.